(untitled) (CIPEEX, 2022)
IN THE FOLLOWING WORK, A DEMONSTRATION OF HOW A HEALTH APP WOULD WORK FOR THE MOSTLY MIDDLE-AGED CUSTOMER WAS PROMOTED. IN A RANGE OF AREA GIVEN BY THE USER’S LOCATION, THE TECMED APPLICATION WOULD SHOW THE NEAREST HOSPITALS AND HEALTH CENTERS WITH THE EASIEST ACCESS TO THE CUSTOMER. ITS SYSTEM ALSO INCLUDES DOCTORS REGISTERED IN HOSPITALS AND THEIR RESPECTIVE LATTES, IN ADDITION TO THE USER’S PREFERENCE FOR THE HEALTH PROFESSIONALS INCLUDED IN THE APP. IT IS ALSO AVAILABLE WHICH FORMS OF PAYMENT ARE ACCEPTED BY SERVICE INSTITUTIONS TO PROVIDE MAXIMUM INFORMATION AND GREATER EFFICIENCY TO USERS IN SCHEDULING APPOINTMENTS.